Impact of maternal HIV–HBV coinfection on pregnancy outcomes in an underdeveloped rural area of southwest China. Issue 7 (7th January 2020) - Li, Chunlin; Yang, Yu; Wang, Yingjian; Dong, Shurong; Yang, Ya; Shi, Ying; Li, Linhan; Jiang, Feng; Chen, Yue; Jiang, Qingwu; Zhou, Yibiao
Abstract : Objectives: Our objective was to determine the impact of maternal HIV–hepatitis B virus (HBV) coinfection on pregnancy outcomes. Methods: The current study was conducted in a county of Yi Autonomous Prefecture in southwest China. Data were abstracted from hospitalisation records, including maternal and infant information. The seroprevalences of HIV and HBV infections and HIV–HBV coinfection were determined and the impact of maternal HIV–HBV coinfection on adverse pregnancy outcomes was assessed using logistic regression analysis. A treatment effects linear regression model was also applied to examine the effect of HBV, HIV or coinfection to quantify the absolute difference in birth weight from a reference of HBV–HIV negative participants. Results: A total of 13 198 pregnant women were included in our study, and among them, 99.1% were Yi people and 90.8% lived in rural area. The seroprevalences of HIV and HBV infections and HIV–HBV coinfection were 3.6% (95% CI: 3.2% to 3.9%), 3.2% (95% CI: 2.9% to 3.5%) and 0.2% (95% CI: 0.1% to 0.2%) among the pregnant women, respectively. Maternal HIV–HBV coinfection was a risk factor for low birth weight (adjusted OR (aOR)=5.52, 95% CI: 1.97 to 15.40). Compared with the HIV mono-infection group, the risk of low birth weight was significantly higher in the HIV–HBV coinfection group (aOR=3.62, 95% CI: 1.24 to 10.56). Maternal HIV infection was associated with an increased risk of low birth weight (aOR=1.90, 95% CI: 1.38 to 2.60) and preterm delivery (aOR=2.84, 95% CI: 1.81 to 4.47). Perinatal death was more common when mothers were infected with HBV (aOR=2.85, 95% CI: 1.54 to 5.26). Conclusions: The prevalence of HIV infection was high among pregnant women of the Yi region. Both HIV and HBV infections might have adverse effects on pregnancy outcomes. Maternal HIV–HBV coinfection might be a risk factor for low birth weight in the Yi region, which needs to be confirmed.